KAJIAN PENGGUNAAN TANAMAN HERBAL DI KALIMANTAN UNTUK MENDUKUNG PRODUKSI ASI PADA IBU MENYUSUI - Haulaini, Shahiroh (Jurnal Farmasindo: Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Indonesia’s tropical climate nurtures a rich biodiversity, including various herbal plants that can enhance maternal and infant health. A significant focus of the government is addressing the low rate of exclusive breastfeeding, which contributes to stunting in children. This study explores herbal plants in Kalimantan that serve as galactagogues, promoting breast milk production in nursing mothers. Research was conducted using academic databases like Scopus, PubMed, and Google Scholar, resulting in five comprehensive scientific articles. The literature review highlights several plants known to increase breast milk production, such as Moringa oleifera (moringa), Curcuma domestica (turmeric), Stenochlaena palustris (kelakai), and a blend of soy milk and dates. Additionally, plants like Chenopodium sp. (village spinach), Ipomoea batatas (sweet potato), and Ocimum basilicum (basil) have shown promising results. Many of these plants are easy to cultivate in home gardens, offering natural solutions to support exclusive breastfeeding initiatives in Indonesia. Utilizing local Kalimantan herbal plants presents an effective alternative for enhancing maternal and infant health and holds potential for further application in the medical field.